Serum Monoamine Oxidase (A and B) Activities and Oxidative Stress Status in Iraqi Infertile Women Undergoing In Vitro Fertilization - Shatha Abdul Wadood Al- Shammaree (Journal of Global Pharma Technology, 2016)
Serum monoamine oxidase (MAO-A and B) activities were measured in 98 infertile women undergoing in vitro fertilization (Intracytoplasmic Sperm Injection ICSI) attending Kamal AL-Samaree Hospital for Infertility and In Vitro Fertilization at Baghdad after treatment with standard long protocol. Methods: Participants in the study were 98 infertile women subdivide according to infertility cause into PCOS, Unknown cause, and Male factor cause. The activities of MAOs, some antioxidant, and oxidant parameters (catalase, thiol levels, and lipid peroxidation product (MDA) were measured. Luteinizing hormone (LH), Follicle stimulating hormone (FSH), LH/FSH ratio, TSH and prolactin were measured. Results: The activities show significant variations among the three infertility groups. Serum MAOs activities (MAO-A, MAO-B) in sera of PCOS (P<0.01), as well, MDA, and total thiol levels were higher significantly when compared with other groups .While, the activity of catalase was lower significantly (p<0.001). Conclusion: Our study reveals the existence of an imbalance between serum oxidant and antioxidant status in infertile women with PCOS undergoing IVF.Keywords: Monoamine Oxidase Activity, Ovary Polycystic Syndrome, Unknown Infertility, Oxidative Stress.